Elements of Work Environment In The Construct Of Special Education Teacher Workload In Malaysia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Work environment can be defined as an environmental condition within the scope of one’s task performance. For a teacher, the work environment is a situation in which the teachers perform their duties in a school organization. While for the scope of special education, the work environment is the state of work and the relationship between teachers, staff, students, administrators and parents. A harmonious and conducive work environment can help the execution of tasks in an orderly and perfect manner. A harmonious work environment is also able to build a good and excellent school. Therefore, this brief study was conducted to explore in more detail the elements of the work environment in providing a good commitment to the school. This qualitative study involved 11 coordinators in the state of Johor, Malaysia. It is hoped that these findings will be able to give a good impact to the next researcher in explaining about this issue.